Risk of febrile seizure after measles–mumps–rubella–varicella vaccine: A systematic review and meta-analysis. Issue 31 (17th July 2015) - Ma, Shu-Juan; Xiong, Yi-Quan; Jiang, Li-Na; Chen, Qing
Highlights: We use systematic strategy and broad search terms in multiple databases and websites. We use rigorous methods to extract and appraise the data. Both clinical trials and post-marketing observations are included to analyze. MMRV vaccine increases potential risk of febrile seizure during second observed week. We provide evidence-based knowledge of febrile seizure risk after MMRV vaccine. Abstract: Background: Considering the febrile seizure rate, there is no longer a clear preference for use of measles–mumps–rubella–varicella (MMRV) vaccine over separate measles–mumps–rubella (MMR) and varicella (V) vaccine. This work was undertaken to assess the risk of febrile seizure after MMRV vaccine in children. Methods: We searched PubMed, Embase, BIOSIS Previews, Scopus, Web of Science, Cochrane Library and other databases through 12 December 2014. Meta-analysis was conducted using R version 3.1.2 and Stata version 12.0. Results: A total of thirty-nine studies were included. Thirty-one published or unpublished clinical trials involving about 40, 000 subjects did not show significant differences in incidence of febrile seizure or vaccine related febrile seizure between MMRV and MMR with or without varicella vaccine after any doses, in the risk windows of 0–28, 0–42 or 0–56 days and 7–10 days. In addition, these studies showed that the receipt of concomitant use of MMRV and other pediatric vaccines was not a significant predictor of febrile seizure. Eight post-marketing observations involving more than 3, 200, 000 subjects were included. No evidence suggested elevated risk of febrile seizure associated with MMRV vaccine among children aged 4–6 years old during 7–10 days or 0–42 days after vaccination. However, an approximately 2-fold increase in risk of seizure or febrile seizure during 7–10 days or 5–12 days after MMRV vaccination was found among children aged 10–24 months, although the highest incidence of seizure was still lower than 2.95‰. Conclusions: First MMRV vaccine dose in children aged 10–24 months was associated with an elevated risk of seizure or febrile seizure. Further post-marketing restudies based on more rigorous study design are needed to confirm the findings.